(3GdYde GdeTghQ aj aVGFd GdCjGe hGdTghQs - (3GdMGaX eLO GdOjf CHj GdNWGH YeQ Hf MSf Hf Ydj Hf hLjI GdcdHj,J (B633 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdSdWGf CHG GdeXaQ eMeO ai aVd GdCjGe hGdTghQ dGRGdJ bdhH CYOGFg NGabI dNabGf CYdGeg hdGHQMJ CQRGb ChdjGFg s
(3BNQgG (B:s
(3cGdchGcH GdeJhbOI s
(3hgh cJGH eHShW ai aVGFd GdCjGe hGdTghQ Ydi WQjbI GdeMOKjf ChQO ajg GdeDda GdTghQ eQJHI hPcQ eG jJUd Hcd TgQ ef aVGFd hCfSGH hdZI hfMh hZQjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1161s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs